Variance risk premiums of commodity ETFs - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2017)
We propose a model-independent method to account for the early exercise premiums in American options on non-dividend paying stocks. We find that our estimates of early exercise premium are generally larger than the estimates by existing methods. Given the American options on the Exchange-Traded Funds (ETFs) of gold, silver, natural gas, and crude oil, we find strong empirical evidence of variance risk premiums for these commodities, over a volatility term structure up to 18 months. Furthermore, we show that volatility indexes constructed by using existing methods tend to overestimate the risk-neutral variance, and consequently the magnitude of variance risk premium.